Effects of dietary vegetable oil on atlantic salmon hepatocyte fatty acid desaturation and liver fatty acid compositions - Tocher, Douglas R.; Bell, J. Gordon; Dick, James R.; Crampton, Viv O. (Lipids, 2003)
Abstract Fatty acyl desaturase activities, involved in the conversion of the C 18 EFA 18∶2n−6 and 18∶3n−3 to the highly unsaturated fatty acids (HUFA) 20∶4n−6, 20∶5n−3, and 22∶6n−3, are known to be under nutritional regulation. Specifically, the activity of the desaturation/elongation pathway is depressed when animals, including fish, are fed fish oils rich in n−3 HUFA compared to animals fed, vegetable oils rich in C 18 FFA. The primary aims of the present study were (i) to establish the relative importance of product inhibition (n−3 HUFA) vs. increased substrate concentration (C 18 EFA) and (ii) to determine whether 18∶2n−6 and 18∶3n−3 differ in their effects on the hepatic fatty acyl desaturation/elongation pathway in Atlantic salmon ( Salmo salar ). Smolts were fed 10 experimental diets containing blends of two vegetable oils, linseed (IO), and rapeseed oil (RO), and fish oil (FO) in a triangular mixture design for 50 wk. Fish were sampled after 32 and 50 wk, lipid and FA composition of liver determined, fatty acyl desaturation/elongation activity estimated in hepatocytes using [1‐ 14 C]18∶3n−3 as substrate, and the data subjected to regression analyses. Dietary 18∶2n−6 was positively correlated, and n−3 HUFA negatively correlated, with lipid content of liver. Dietary 20∶5n−3 and 22∶6n−3 were positively correlated with liver FA with a slope greater than unity suggesting relative retention and deposition of these HUFA. In contrast, dietary 18∶2n−6 and 18∶3n−3 were positively correlated with liver FA with a slope of less than unity suggesting metabolism via β‐oxidation and/or desaturation/elongation. Consistent with this, fatty acyl desaturation/elongation in hepatocytes was significantly increased by feeding diets containing vegetable oils. Dietary 20∶5n−3 and 22∶6n−3 levels were negatively correlated with hepatocyte fatty acyl desaturation. At 32 wk, 18∶2n−6 but not 18∶3n−3 was positively correlated with hepatocyte fatty acyl desaturation, wheres the reverse was true at 50 wk. The data indicate that both ...